Low night temperature and water deficit on photosynthesis of sugarcane - Machado, Daniela Favero São Pedro; Lagôa, Ana Maria Magalhães Andrade; Ribeiro, Rafael Vasconcelos; Marchiori, Paulo Eduardo Ribeiro; Machado, Ricardo Silvério; Machado, Eduardo Caruso (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the photosynthetic responses of sugarcane to the simultaneous and isolated effects of low night temperature (TN) and water deficit (DH). After 128 days of planting, plants of the cultivar IACSP94-2094 were subjected to the following treatments: control, without DH and with TN of 20°C (TN20); with DH and TN of 20°C (DH/TN20); without DH and with TN of 12°C (TN12); and with DH and TN of 12°C (DH/TN12). After the period of treatment, plants were irrigated and subjected to TN of 20°C for four more days, for recovery. There were decreases in CO2 assimilation in all treatments. Total recovery of CO2 assimilation was observed only in plants from the treatment TN12. The simultaneous occurrence of low night temperature and water deficit caused a accentuated and persistent effect on stomatal conductance, on the maximum capacity of ribulose‑1,5‑bisphosphate carboxylase, on the electron transport rate, on the efficiency factor, and on the operational efficiency of photosystem II, which resulted in diffusive, biochemical, and photochemical limitations of photosynthesis of sugarcane plants.